Differential expression of the IRF6 gene in the signs of Van der Woude Syndrome: Are distinct genetic modifiers operating? - Rosany de Oliveira Lisboa; Cláudia Maria da Rocha Martins; Maria Elisabete Silva Santos; Danilo Leôncio Aguiar Pereira; Flávia Martinez de Carvalho; Ieda Maria Orioli; João Farias Guerreiro; Alexandre Rezende Vieira; Luiz Carlos Santana- (University Library System, University of Pittsburgh, 2021)
Objective: The purpose of this study was to report a new variant in the Interferon Regulatory Factor 6 gene (IRF6) and to determine phenotype-genotype correlations in a family segregating Van der Woude syndrome. Methods: A five-generation family of 80 individuals segregating VWS was investigated using a tabulated pedigree but considering that three individuals registered in the pedigree died shortly after birth, the final sample size was 77 individuals.  Five individuals had a complete dental clinical examination and molecular analysis performed using direct sequencing of the exon 4 and an adjacent region with 23 base pairs of the IRF6 gene. Results: Features of VWS reported in family history were present in 36.4% (28/77) of all family members; of these 57% (16/28) had pits in the lower lip, 36% (10/28) had both pits and orofacial clefts and 7 % (2/28) had only orofacial clefts. Developmental dental anomalies were observed in three individuals. The sequence analysis of exon 4 of the IRF6 gene carried out for 4 family members revealed the presence of the SNP rs7552506 (c.175-5C> G) located in five base pairs before the start of exon. The analysis of exon 4 of the IRF6 gene also revealed a new variant c.269G>C (p.Ser90Thr) which causes exchange of the Serine amino acid residue for the Threonine residue.  Conclusions: The c.269G>C(p.Ser90Thr) can interfere with multimeric interactions and with protein conformation that will be slightly destabilized, because the mutant residue is bigger than the wild-type residue. The phenotypic variations in the cases studied, despite carrying the same genetic mutation, suggest that distinct genetic modifiers operate on the formation of clefts and dental development.